The Social Status of Languages in Finland and Lithuania A Plurimethodological Empirical Survey on Language Climate Change - Kessler, Stephan; Pantermöller, Marko (Sprachkoennen und Sprachbewusstheit in Europa / Language Competence and Language Awareness in Europe, 2020)
Finland and Lithuania stand for different ways of dealing with societal multilingualism and minority issues. However, in recent years, questions of language policy had been discussed more controversially in both countries. Thus our detailed surveys on Finland and Lithuania focused on how different population groups think about the lingual situation there. This publication presents the researchers' results from between 2014 and 2016 regarding the attitudes towards the minority and majority languages. Key to the research was an especially developed methodological mixture, including the matched-guise technique. The surveys' final reports to the German Research Foundation (DFG) are followed by contributions that give more details on the legal status of the languages in Finland and Lithuania or describe the specific features of urban multilingualism there.